Reactulization of Islamization of Islamic Science and Knowledge in an Ontological-Historical Perspective for the Development of UIN K.H. Abdurrahman Wahid - Batsnah Nuwaifila (Yayasan Insan Cendekia Nusantara, 2024)
The development of Science and Technology (IPTEK) now universities in Indonesia also adopt technology in education, especially in Islamic education (UIN). This is an interesting thing in this study. Which is a form of Islamization of science that is increasingly growing. The formulation of the problem in this study is “How to actualize the Islamization of Islamic science and science in education for the development of UIN KH. Abdurrahman wahid?